2013
DOI: 10.1016/j.plipres.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The plant non-specific phospholipase C gene family. Novel competitors in lipid signalling

Abstract: Non-specific phospholipases C (NPCs) were discovered as a novel type of plant phospholipid-cleaving enzyme homologous to bacterial phosphatidylcholine-specific phospholipases C and responsible for lipid conversion during phosphate-limiting conditions. The six-gene family was established in Arabidopsis, and growing evidence suggests the involvement of two articles NPCs in biotic and abiotic stress responses as well as phytohormone actions. In addition, the diacylglycerol produced via NPCs is postulated to parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 211 publications
4
97
0
Order By: Relevance
“…ZmPLC1 from maize ( Zea mays L .) is up-regulated in response to dehydration [50], and enhanced expression of sense ZmPLC1 has been shown to improve the drought tolerance of maize plants [19], [51]. In this study, we found that TaPLC1 expression in wheat was induced in response to high salt and drought stress at both the mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 60%
“…ZmPLC1 from maize ( Zea mays L .) is up-regulated in response to dehydration [50], and enhanced expression of sense ZmPLC1 has been shown to improve the drought tolerance of maize plants [19], [51]. In this study, we found that TaPLC1 expression in wheat was induced in response to high salt and drought stress at both the mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 60%
“…We found that DEGs showing similarity to, inter alia , non-specific phospholipase C (NPC), belonged to this pathway. NPCs play important roles in many processes as phospholipid-to-galactosyl DAG exchange, growth and development associated with hormone signaling and stress responses (reviewed in: Pokotylo et al, 2013). The same phospholipases were included in the “Ether lipid metabolism” and “Glycerophospholipid metabolism” pathways that were strongly up-regulated in the abscising flower pedicels.…”
Section: Discussionmentioning
confidence: 99%
“…Two types of PLCs are known: non-specific PLC (NPC) and phosphoinositide-specific PLC (PI-PLC). NPC hydrolyzes major phospholipid classes such as PC and PE and is found only in bacteria [90] and higher plants [91,92]. PI-PLC specifically hydrolyzes PI or its phosphorylated derivatives (phosphoinositides, PIPn) such as PI 4,5-bisphosphate (PI(4,5)P 2 ).…”
Section: Phospholipase C (Plc)mentioning
confidence: 99%